2014
DOI: 10.1039/c3cp54634a
|View full text |Cite
|
Sign up to set email alerts
|

The nature of coherences in the B820 bacteriochlorophyll dimer revealed by two-dimensional electronic spectroscopy

Abstract: Light-harvesting in photosynthesis is determined by the excitonic interactions in disordered antennae and the coupling of collective electronic excitations to fast nuclear motions, producing efficient energy transfer with a complicated interplay between exciton and vibrational coherences. Two-dimensional electronic spectroscopy (2DES) is a powerful tool to study the presence of these coherences in photosynthetic complexes. However, the unambiguous assignment of the nature of the observed coherences is still un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 36 publications
6
70
0
Order By: Relevance
“…Coherence beatings can be analyzed by performing the Fourier transform of the time traces of the peaks. A very convenient way to represent the overall complexity of oscillations in the 2D spectrum is through the Fourier maps [36][37][38][39][40][41] . They are constructed by performing the Fourier transform of the each data point in the 2D spectrum over the delay time t 2 after subtraction of slow exponential decay contributions.…”
Section: Resultsmentioning
confidence: 99%
“…Coherence beatings can be analyzed by performing the Fourier transform of the time traces of the peaks. A very convenient way to represent the overall complexity of oscillations in the 2D spectrum is through the Fourier maps [36][37][38][39][40][41] . They are constructed by performing the Fourier transform of the each data point in the 2D spectrum over the delay time t 2 after subtraction of slow exponential decay contributions.…”
Section: Resultsmentioning
confidence: 99%
“…However, n ≥ 2 is necessary for s h to be finite in Eq. (16 is usually observed that J(ω) → 0 as ω → 0 44 what is possible when n ≥ 3.…”
Section: A Limitations Of the Linear System-bath Coupling Modelmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Probably, the milestone advancement of the technique was direct demonstration of electronic and vibrational, as well as mixed, quantum coherences via femtosecond beats of various diagonal and off-diagonal peaks in the 2D plots from 77 K up to room temperature. 1,5,7,[13][14][15][16][17][18] These results attained much interest and caused intensive debates on the origin and functional purpose of the oscillations: whether they arise from quantum excitation dynamics in bio-materials purposefully optimized by nature, or the oscillations record merely bond wiggling, which is natural and not necessarily a quantum phenomenon. 5,7,16,[19][20][21][22][23][24][25][26] However, it has been acknowledged that nuclear dynamics and its coupling to the electronic excitations leads to the important physical dynamic processes leading to energy photoconversion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,11,34,35 A number of synthetic and biological dimers which sample different parameter regimes have been described, which would serve as very interesting systems to test the practical application of this experiment. [58][59][60][61][62][63][64][65] It is important to note that there are a number of practical difficulties that might limit the general applicability of the approach described in this work. In particular, it crucially relies on the ability to resolve the spectral features corresponding to each exciton and to a vibration on each site in the 2DEV spectra.…”
Section: Discussionmentioning
confidence: 99%